Kratosvirus quantuckense: the history and novelty of an algal bloom disrupting virus and a model for giant virus research - Truchon, Alexander R.; Chase, Emily E.; Gann, Eric R.; Moniruzzaman, Mohammad; Creasey, Brooke A.; Aylward, Frank O.; Xiao, Chuan; Gobler, Christopher J.; Wilhelm, Steven W. (Frontiers in Microbiology, 2023)
Since the discovery of the first "giant virus", particular attention has been paid towards isolating and culturing these large DNA viruses through Acanthamoeba sp. bait systems. While this method has allowed for the discovery of plenty novel viruses in the Nucleocytoviricota, environmental -omics-based analyses have shown that there is a wealth of diversity among this phylum, particularly in marine datasets. The prevalence of these viruses in metatranscriptomes points towards their ecological importance in nutrient turnover in our oceans and as such, in depth study into non-amoebal Nucleocytoviricota should be considered a focal point in viral ecology. In this review, we report on Kratosvirus quantuckensis (née Aureococcus anophagefferens Virus), an algae-infecting virus of the Imitervirales. Current systems for study in the Nucleocytoviricota differ significantly from this virus and its relatives, and a litany of trade-offs within physiology, coding potential, and ecology compared to these other viruses reveal the importance of K. quantuckense. Herein, we review the research that has been performed on this virus as well as its potential as a model system for algal-virus interactions.